2009
DOI: 10.1017/s0007114509991553
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and non-steroidal anti-inflammatory drugs on human intestinal microbiota composition

Abstract: Ageing has been suggested to cause changes in the intestinal microbial community. In the present study, the microbiota of a previously welldefined group of elderly subjects aged between 70 and 85 years, both non-steroidal anti-inflammatory drugs (NSAID) users (n 9) and nonusers (n 9), were further compared with young adults (n 14) with a mean age of 28 years, by two DNA-based techniques: percentage guanine þ cytosine (%G þ C) profiling and 16S rDNA sequencing. Remarkable changes in microbiota were described wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
174
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(191 citation statements)
references
References 51 publications
15
174
2
Order By: Relevance
“…21 Similarly, variable results have also been observed for lactobacilli, with some studies reporting a reduction 22,28 and others an increase in the levels of these microorganisms at older ages. 24,27,29 It is still unclear whether this variability in the results obtained for certain microbial groups is related to actual population differences or to methodological issues, such as the different techniques used for determining microbial abundancies ( Table 1).…”
Section: The Gut Microbiome: Composition Functionality and Evolutionmentioning
confidence: 99%
“…21 Similarly, variable results have also been observed for lactobacilli, with some studies reporting a reduction 22,28 and others an increase in the levels of these microorganisms at older ages. 24,27,29 It is still unclear whether this variability in the results obtained for certain microbial groups is related to actual population differences or to methodological issues, such as the different techniques used for determining microbial abundancies ( Table 1).…”
Section: The Gut Microbiome: Composition Functionality and Evolutionmentioning
confidence: 99%
“…A decrease of Clostridium cluster XIVa in elderly persons was reported by Biagi et al [38]. Mueller et al [49] and Makivuokko et al [51] found that such a change was dependent on the nationality of the volunteer.…”
Section: Intestinal Microbiota Changes In An Aging Populationmentioning
confidence: 74%
“…Also, by using fluorescence in situ hybridisation (FISH) Mueller et al [49] found this trend in Italian elderly. Furthermore, increased Bacteroides have been reported in Austrian elderly patients [50] and Finnish elderly subjects [51] by using molecular methods.…”
Section: Intestinal Microbiota Changes In An Aging Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, faecal polyamine concentrations provide supporting evidence of higher polyamine concentrations within the gut in young and healthy adults compared with the elderly. For example, the concentration of spermidine in the faeces of the elderly was found to be significantly less than that in healthy young adults, and this was linked with changes to gut microbiota (Mäkivuokko et al, 2010). Further evidence suggests that hospitalised elderly subjects have significantly lower intestinal polyamine concentrations than healthy adults, and polyamine concentration was significantly influenced by the faecal microflora pattern present between the two groups (Matsumoto & Benno, 2007).…”
Section: Gut Healthmentioning
confidence: 99%